PENTINGNYA PENDIDIKAN KARAKTER PADA ANAK USIA DINI DALAM MENGHADAPI ERA GLOBALISASI - Rohayu Fadilla; Bela Ananda; Amelia Septriani; Julisa Komala (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the importance of character education in early childhood in facing the era of globalization. The research uses a qualitative descriptive approach with a literature study method. Data were collected through documentation of relevant journals, books, and previous studies, then analyzed using content analysis. The results show that character education plays a crucial role in shaping children’s morals, attitudes, and social behavior during the golden age. Globalization brings both positive and negative impacts, especially through digital technology exposure. Therefore, collaboration between family, school, and society is essential in strengthening character education from an early age.